Reprogramming the tumor microenvironment to overcome immunotherapy resistance in pancreatic cancer - Hui, Xianfeng; Tian, Xiaowei; Ding, Shihuan; Sun, Aiping; Zhao, Tiesuo; Wang, Hui (Frontiers in Immunology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) exhibits profound resistance to immunotherapy due to its highly immunosuppressive tumor microenvironment (TME).ObjectiveThis review aims to elucidate the key mechanisms of TME-mediated immune evasion in PDAC and explore therapeutic strategies to overcome these barriers.MethodsA comprehensive analysis of recent studies was conducted, focusing on the cellular, stromal, and metabolic components of the PDAC TME, alongside emerging technologies for TME reprogramming.ResultsDense extracellular matrix, CAF-driven fibrosis, myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs), Tregs, and metabolic competition collectively impair immune cell infiltration and activation. Novel interventions—including ECM remodeling, CAF modulation, metabolic reprogramming, and myeloid cell targeting—show promise in restoring immune responsiveness.ConclusionTME reprogramming represents a critical strategy to enhance immunotherapy efficacy in PDAC, offering new opportunities for overcoming immune exclusion and resistance.